2019
DOI: 10.3390/cancers11050656
|View full text |Cite
|
Sign up to set email alerts
|

Countering TRAIL Resistance in Melanoma

Abstract: Melanoma of the skin has become a prime example for demonstrating the success of targeted cancer therapy. Nevertheless, high mortality has remained, mainly related to tumor heterogeneity and inducible therapy resistance. But the development of new therapeutic strategies and combinations has raised hope of finally defeating this deadly disease. TNF-related apoptosis-inducing ligand (TRAIL) represents a promising antitumor strategy. The principal sensitivity of melanoma cells for TRAIL was demonstrated in previo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 113 publications
(186 reference statements)
1
44
0
Order By: Relevance
“…Apoptosis resistance represents a critical hallmark in cancer, 4 and the targeting of apoptosis pathways, for example, by the death ligand TRAIL, appears as a promising antitumor strategy. 18 The particular advantage of TRAIL is based on its capability to selectively induce apoptosis in cancer cells, while normal cells are largely spared. 13,14 TRAIL agonists have proven good tolerability and safety profiles in clinical trials, however, an additional clinical benefit, when TRAIL was applied in combination therapies, so far remained on a low level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apoptosis resistance represents a critical hallmark in cancer, 4 and the targeting of apoptosis pathways, for example, by the death ligand TRAIL, appears as a promising antitumor strategy. 18 The particular advantage of TRAIL is based on its capability to selectively induce apoptosis in cancer cells, while normal cells are largely spared. 13,14 TRAIL agonists have proven good tolerability and safety profiles in clinical trials, however, an additional clinical benefit, when TRAIL was applied in combination therapies, so far remained on a low level.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the control of mitochondrial apoptosis pathways came into particular focus for explaining TRAIL resistance in melanoma. 17,18 Mitochondrial apoptosis pathways are decisively controlled by the family of Bcl-2 proteins, which share one to four distinct Bcl-2 homology (BH) domains. Bcl-2 proteins interact and control each other by heterodimerization.…”
mentioning
confidence: 99%
“…The MDR phenotype of breast cancer cells was associated with abnormal activation of the PI3K/AKT/NF-κB signaling pathway 67 . Constitutive and inducible activation of PI3K/AKT/NF-κB in cancer cells (such as pancreatic cancer) are closely related to tumorigenesis and promoted MDR-like cell proliferation and apoptosis 68 . Ni et al reported that MDR of nasopharyngeal carcinoma (NPC) was reversed by inhibition of the PI3K/AKT/NF-κB signaling pathway.…”
Section: Pi3k/akt/nf-κbmentioning
confidence: 99%
“…Cancer cells manage to grow and survive after hijacking TRAIL-mediated apoptosis ( 116 ). Tumor cells use Fas receptor as a reserve route to initiate activation of caspase 8 via proteolytic cleavage and hence induce apoptosis ( 117 , 118 ). In breast cancer, the expression levels of Fas and FasL are also downregulated, eliminating all apoptotic threats for cancerous cells and making their proliferation possible ( 119 ).…”
Section: Interplay Of Lncrna and Trail In Breast Cancermentioning
confidence: 99%